Analisis Rantai Nilai Kopi untuk Meningkatkan Nilai Tambah Petani Kopi di Kecamatan Paguyangan Brebes - Umroh, Siti Badiatul; sutarmin, sutarmin; Nurmeilinda, Kharisma; Purwanti, Eri Nanda Dewi (CV. ITTC INDONESIA, 2024)
The current coffee potential in Brebes Regency has not been accompanied by high income for coffee farmers. This is because farmers' knowledge of how to maintain coffee plants is still very low, farmer organizations are weak and government support is limited. Until now, coffee has not been considered a crop of strategic importance. The purpose of this study was to identify coffee commodity resources, analyze the value chain and determine cost drivers. This study used a mixed research approach of both qualitative and quantitative research. The qualitative research approach was to answer the research questions posed. Quantitative research in this study is to calculate the cost value of each process activity in coffee processing. Based on the value chain analysis, the determinants of downstream coffee processing products are greenbean processing, roasting and grinding. Greenbean processing is able to add value by 47.5% for robusta type and 71.47% for arabica coffee type. While roasting and grinding activities are able to increase the added value by 65.36% for robusta type and 85.12% for arabica type.